Assistance for Legal Aspects of Digital Start-Ups at the Incubation Stage - Destyarini, Normalita (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement), 2023)
The development of business entities by utilizing technology in this case digital startups makes it necessary to see the problems of legal aspects faced by partners in this case digital startups business entities at the incubation stage. The purpose of community service is to provide an understanding of the fulfillment of legal aspects for digital startups business entities. The service method is carried out by selecting partners, determining the title of the service, conducting preliminary research, preparing an activity proposal and applying for a license to carry out the service. The results of this community service have found that there are still obstacles related to the legality process for business entities in this case determining the form of business entity that will be used in running their business, so it is necessary to provide further legal aspects assistance related to taxation and intellectual property in the form of brands owned by business entities.